P060 Co-morbidity of delayed sleep phase and psychiatric conditions in a cohort of adolescents. (19th November 2019) - Kuula, Liisa; Pesonen, Anu-Katriina
Abstract : Introduction: Delayed Sleep Phase (DSP) is an extremely common sleep problem during adolescence. It is typically manifested as frequently occurring late bedtimes and difficulties waking up. The prevalence in entire populations is estimated to be over 15%. While it is common in typically developing teenagers (estimates ranging from 15%-50%), its prevalence may be even higher in those suffering from psychiatric conditions such as severe depression or anxiety. Methods: We studied a cohort sample (n=295) of 17-year-olds (70% girls) in order to detect co-morbidity of DSP and several psychiatric disorders. For sleep measurements we used actigraphy (GeneActiv Original) for a minimum of 7 days as well as the Pittsburgh Sleep Quality Index. These served as tools for estimating a tendency towards DSP, which was defined as having a bedtime later than 1 AM for more than three times per week. Psychiatric disorders (major depressive disorder, generalized anxiety disorder, hypo-manic disorders, obsessive-compulsive disorder, psychotic disorders, and eating disorders) were evaluated using a validated MINI structured interview. Results: The overall prevalence of DSP was 50% in our sample of adolescents. There were no differences between girls and boys in the prevalence of DSP (p=0.24). DSP was significantly higher in those with major depressive disorder (p=0.018), generalized anxiety disorder (p=0.025), and almost significant for obsessive-compulsive disorder (p=0.055). DSP was not more prevalent in hypo-manic disorders, psychotic disorders, or any eating disorders (all p-values>0.3). Discussion: We found a significant co-morbidity between DSP and several psychiatric disorders. This suggests that there is an added burden of sleep problems in those with issues relating to mental well-being. As our study population is from a relatively healthy population it is likely that some of the associations remained undetected; for instance, the prevalence of eating disorders was not high enough to examine DSP reliably.